Survey Using the Physical Activity Questionnaire For Older Children (PAQ-C) Upper Class Students of SD N Sugihwaras, Gondang, Bagor, Nganjuk, East Java - Agi Yanuar Primadani; Dhedhy Yuliawan; Ruruh Andayani Bekti (CV. Nusantara Sporta, 2023)
The problems studied in this study are in accordance with observations of physical activity which are still assumed to be lacking by researchers. So that filling out the questionnaire can be done online. The instrument of this study used the Physical Activity Questionaire For Older Children (PAQ-C) with a validity of 0.881 and a reliability of 0.745 formatted in the form. The results showed that the level of physical activity in the analysis of the percentage of upper class students at SD Sugihwaras found 14.02% in the very often category with a frequency of 15 students, 38.32% in the often category with a frequency of 41 students, 44.86% in the sometimes category with a frequency 48 students, 2.80% fall into the sometimes category with a frequency of 3 students, and 0% fall into the never category with a frequency of 0 students. So it can be concluded that the physical activity of the upper grade students at SD Sugihwaras is included in the sometimes category with a frequency of 20 students